How to Make Feedback More Effective? Qualitative Findings from Pilot Testing of an Audit and Feedback Report for Endoscopists - Fiona Webster; Jigisha Patel; Kathleen Rice; Nancy Baxter; Lawrence Paszat; Linda Rabeneck; Jill Tinmouth (Canadian Journal of Gastroenterology and Hepatology)
Background. Audit and feedback (A/F) reports are one of the few knowledge translation activities that can effect change in physician behavior. In this study, we pilot-tested an endoscopist A/F report to elicit opinions about the proposed report’s usability, acceptability and usefulness, and implications for knowledge translation. Methods. Semi-structured qualitative interviews were conducted with eleven endoscopists in Ontario, Canada. We tested an A/F report template comprising 9 validated, accepted colonoscopy quality indicators populated with simulated data. Interview transcripts were coded using techniques such as constant comparison and themes were identified inductively over several team meetings. Results. Four interrelated themes were identified: (1) overall perceptions of the A/F report; (2) accountability and consequences for poor performance; (3) motivation to change/improve skills; and (4) training for performance enhancement and available resources. The A/F report was well received; however, participants cited some possible threats to the report’s effectiveness including the perceived threat of loss of privileges or licensing and the potential for the data to be dismissed. Conclusions. Participants agreed that A/F has the potential to improve colonoscopy performance. However, in order to be effective in changing physician behavior, A/F must be thoughtfully implemented with attention to the potential concerns of its recipients.